Effects of Unionization on Workplace-Safety Enforcement: Regression-Discontinuity Evidence - Aaron J. Sojourner; Jooyoung Yang (Institute for the Study of Labor (IZA), 2015)
We study how union certification affects the enforcement of workplace-safety laws. To generate credible causal estimates, a regression discontinuity design compares outcomes in establishments where unions barely won representation elections to outcomes in establishments where union barely lost such elections. The study combines two main datasets: the census of National Labor Relations Board (NLRB) representation elections and the Occupational Safety and Health Administration's (OSHA) enforcement database since 1985. There is evidence of positive effects of union certification on establishment's rate of OSHA inspection, the share of inspections carried out in the presence of a labor representative, violations cited, and penalties assessed.
Keywords: J51; J28; I18; 330; union(s); OSHA inspections; workplace accidents; effects; labor market institutions